1995
DOI: 10.1002/aja.1002020305
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine, a steroidal alkaloid, disrupts development of cranial neural crest cells in Xenopus

Abstract: Cyclopamine is a steroidal alkaloid which causes limb and craniofacial defects in many vertebrate species. We have used Xenopus Zaeuis as a model system to characterize the defects caused by cyclopamine at the cellular level. The most dramatic consequence of cyclopamine treatment in the Xenopus embryo is a defect in formation of craniofacial cartilage. Much of this cartilage is absent in treated animals. As in avian and mammalian species, Xenopus craniofacial cartilage is derived primarily from cells of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Furthermore, analyses of the timing and tissue requirements for Shh signaling reveal a direct requirement for Hh signal transduction within DRG precursors, and suggest that Shh signaling may act upstream of Ngn1 to promote the specification of DRG neurons. These studies add to the previously demonstrated roles for Shh signaling in other aspects of neural crest development, particularly craniofacial development (Dunn et al, 1995;Ahlgren and Bronner-Fraser, 1999). In addition to the prevalent loss of DRG in midline/Hh mutants and in cyclopamine-treated embryos, in some segments we observed the appearance of abnormal neuronal clusters ventrolateral to the spinal cord.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, analyses of the timing and tissue requirements for Shh signaling reveal a direct requirement for Hh signal transduction within DRG precursors, and suggest that Shh signaling may act upstream of Ngn1 to promote the specification of DRG neurons. These studies add to the previously demonstrated roles for Shh signaling in other aspects of neural crest development, particularly craniofacial development (Dunn et al, 1995;Ahlgren and Bronner-Fraser, 1999). In addition to the prevalent loss of DRG in midline/Hh mutants and in cyclopamine-treated embryos, in some segments we observed the appearance of abnormal neuronal clusters ventrolateral to the spinal cord.…”
Section: Discussionsupporting
confidence: 75%
“…Injection of function-blocking anti-Shh antibody into chick cranial mesenchyme results in a loss of branchial arch structures that is associated with significant cell death in both the neural tube and neural crest (Ahlgren and BronnerFraser, 1999). Similarly, cyclopamine treatment of Xenopus embryos results in a reduction of craniofacial cartilages and promotes cell death in explants of cranial neural crest (Dunn et al, 1995). In our experiments, zebrafish migratory trunk neural crest appears normal in embryos in which Hh signaling is blocked.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A chemical compound, cyclopamine, has been shown to inhibit Shh function highly specifically by binding to its coreceptor Smoothened (Incardona et al, 1998;Chen et al, 2002;Frank-Kamenetsky et al, 2002). Administration of cyclopamine to zebrafish, chicken, and mouse phenocopies the loss-of-function mutation of Shh (Dunn et al, 1995;Incardona et al, 1998;Berman et al, 2002;Chen et al, 2002;Charron et al, 2003). We included cyclopamine in the culture media and repeated the coculture gel culture experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments suggest that the high level of BMP antagonism provided synergistically by both Noggin and Chordin fulfills this protective role. In addition, Chordin and Noggin promote rostral expression of Shh (Anderson et al, 2002), which in turn is essential for cranial neural crest survival (Dunn et al, 1995;Ahlgren and BronnerFraser, 1999). Thus, Chordin and Noggin may protect NCCs from apoptosis induced directly by elevated BMP signaling, and indirectly by maintaining Shh signaling.…”
Section: Bmp Antagonism Is Required For Survival Of Migratory Nccsmentioning
confidence: 99%